2013
DOI: 10.1016/j.jacc.2012.08.1026
|View full text |Cite|
|
Sign up to set email alerts
|

Remnant Cholesterol as a Causal Risk Factor for Ischemic Heart Disease

Abstract: A nonfasting remnant cholesterol increase of 1 mmol/l (39 mg/dl) is associated with a 2.8-fold causal risk for ischemic heart disease, independent of reduced HDL cholesterol. This implies that elevated cholesterol content of triglyceride-rich lipoprotein particles causes ischemic heart disease. However, because pleiotropic effects of the genetic variants studied cannot be totally excluded, these findings need to be confirmed using additional genetic variants and/or randomized intervention trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

36
631
4
13

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 861 publications
(684 citation statements)
references
References 43 publications
36
631
4
13
Order By: Relevance
“…The investigators showed that these genetic elevations in calculated RLP‐C based on nonfasting TG levels were associated with an 87% increased odds of MI. In a slightly expanded study population inclusive of the same Danish cohort, Varbo et al analyzed genetic variants affecting single lipoprotein classes including nonfasting remnants, HDL‐C, and LDL‐C 16. The investigators found a causal odds ratio for ischemic heart disease of 2.8 for each 39‐mg/dL increase in nonfasting remnant cholesterol levels (again, as calculated from TG measurements).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The investigators showed that these genetic elevations in calculated RLP‐C based on nonfasting TG levels were associated with an 87% increased odds of MI. In a slightly expanded study population inclusive of the same Danish cohort, Varbo et al analyzed genetic variants affecting single lipoprotein classes including nonfasting remnants, HDL‐C, and LDL‐C 16. The investigators found a causal odds ratio for ischemic heart disease of 2.8 for each 39‐mg/dL increase in nonfasting remnant cholesterol levels (again, as calculated from TG measurements).…”
Section: Discussionmentioning
confidence: 99%
“…Historically, some studies have suggested that this association is attenuated by the inclusion of other potentially causal factors such as HDL‐C, thus raising the question of whether RLPs may represent a surrogate for other causative factors in atherosclerotic disease 12, 13. Recent Mendelian randomization studies have served as the strongest evidence that RLPs are etiologic for atherosclerosis 6, 14, 15, 16. Further, TGs are predictive of residual risk in statin‐treated individuals 17.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epidemiologic studies have shown that elevated triglycerides correlate with elevated cardiovascular risk,4, 5 and the American Heart Association has long recognized that elevated triglycerides are an important marker of cardiovascular risk 6. More recently, genetic,7, 8, 9, 10, 11, 12, 13 genome‐wide analysis,14, 15, 16, 17 and mendelian randomization18, 19, 20, 21, 22 studies have suggested a causal role for triglycerides as a modifiable risk factor in the development and progression of ASCVD. Analyses from clinical data have demonstrated that lower on‐treatment triglycerides correlate with reduced cardiovascular risk 23, 24…”
mentioning
confidence: 99%
“…These lipid abnormalities, termed diabetic (or mixed) dyslipidemia (Figure), account for their elevated levels of non‐high‐density lipoprotein cholesterol, triglycerides, and small dense LDLs 32, 33. Remnants of triglyceride‐rich lipoproteins, which include chylomicrons and very‐low‐density lipoproteins, have enhanced atherogenic potential since they contain more cholesterol per particle than LDL,34 and have been shown to have a substantial and independent causal association with cardiovascular risk 35. Whereas the LDLR binds to LDLs via apolipoprotein‐B100 (apoB100),36 LDLR binds triglyceride‐rich lipoprotein remnants through interactions with apolipoprotein‐E (apoE), and clearance of these particles occurs along with other receptors such as LDLR‐related protein 1 and Syndecan‐1 37, 38.…”
Section: Mechanism Of Action Of Pcsk9 Inhibitorsmentioning
confidence: 99%